Validation of an Informant-Reported Web-Based Data Collection to Assess Dementia Symptoms - Rockwood, Kenneth; Zeng, An; Leibman, Chris; Mucha, Lisa; Mitnitski, Arnold (JMIR Publications, 2012)
BackgroundThe Web offers unprecedented access to the experience of people with dementia and their care partners, but data gathered online need to be validated to be useful. ObjectiveTo test the construct validity of an informant Web-based data collection to assess dementia symptoms in relation to the 15-point Dependence Scale (DS). MethodsIn an online survey posted on the DementiaGuide website, care partners of people with dementia built individualized profiles from the 60-item SymptomGuide and completed a questionnaire, which included the DS and a staging tool. ResultsIn the 250 profilees (155, 62% women, mean age 77 years), increasing dependence was associated with a greater chance of institutionalization. For example, no one at the lowest levels of dependence (DS score < 5, n = 33) was in long-term care, compared with half (13/25) of the profilees at the highest levels of dependence (DS score > 12) being in institutions (χ24 = 27.9, P < .001). The Web-based DS was correlated with the number of symptoms: higher DS scores were associated with a higher stage of dementia (F > 50, P < .001). ConclusionIn an online survey, the Web-based DS showed good construct validity, potentially demonstrating how the Web can be used to learn more about dementia progression and how it relates to symptoms experienced by patients across the course of dementing illnesses. Even so, caution is needed to assure the validity of data collected online.